Early Permian (Cisuralian) ostracods from Japan: characteristic ostracod assemblage from a seamount of the Panthalassic Ocean - Tanaka, Gengo; Miyake, Yukio; Ono, Teruo; Yuan, Aihua; Ichida, Masahiro; Maeda, Haruyoshi; Crasquin, Sylvie (Zootaxa, 2018)
Silicified ostracods were recovered from Cisuralian micritic limestones of the Ryozensan Limestone Formation from the southwestern part of Ryozensan Mountain, Taga City located in Shiga Prefecture, Central Japan. Twenty-seven species belonging to 19 genera were obtained, of which six species are new and are described here: Bairdia tagaensis Tanaka sp. nov., Bairdiacypris ikeyanoriyukii Tanaka sp. nov., Kellettina noriyukii Tanaka sp. nov., Microcheilinella shigensis Tanaka sp. nov., Oliganisus ryozensannensis Tanaka sp. nov., and Pustulobairdia ohmiensis Tanaka sp. nov. Some Palaeozoic limestone localities in Japan cap greenstones and are surrounded by younger cherts (such as Mino Terrane of this study). They represent a characteristic reef and reef-slope environment around a seamount surrounded by deep sea ocean floor. This result is concordant with the ostracod assemblage. After this report, a Panthalassan ostracod fauna could be defined for the Cisuralian.